Генетична колекція Aegilops biuncialis Vis. - Козуб, Н.О.; Созінов, І.О.; Бідник, Г.Я.; Дем’янова, Н.О.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of the study was to make the genetic collection of Aegilops biuncialis Vis. «Collection of Aegilops
biuncialis Vis. accessions with respect to alleles at the storage protein loci Glu-U1, Glu-Mb
1, Gli-U1, Gli-Mb
1» and
analyze its diversity in comparison with that in Crimean populations. Methods. We used SDS and APAG electrophoresis
to identify alleles at the Glu-1 and Gli-1 loci. Results. In the Ae. biuncialis collection there are 6, 9, 13, and 12 alleles at
the loci Glu-U1, Glu-Mb
1, Gli-U1 and Gli-Mb
1, respectively. In comparison with the allele diversity revealed in Crimean
populations of the species, the collection represents 60% of identified alleles at Glu-U1, 50% of alleles at Glu-Mb
1, 68%
of alleles at Gli-U1, and 100% of alleles at Gli-Mb
1. Conclusions. The Ae. biuncialis collection comprises from 50 to
100% of diversity of alleles at the storage protein loci revealed in Crimean populations and may be considered as the basis
of the core collection from its Crimean part of the area.
Keywords: Aegilops biuncialis Vis., diversity, high-molecular-weight glutenin subunits, gliadin, alleles.